2011
DOI: 10.1007/s10637-011-9728-z
|View full text |Cite
|
Sign up to set email alerts
|

Description of the cytotoxic effect of a novel drug Abietyl-Isothiocyanate on endometrial cancer cell lines

Abstract: The objective of the present study was to determine the in-vitro effect of Abietyl-Isothiocyanate (ABITC), a representative of a new class of anti-cancer drugs, on endometrial cancer (EC) cell lines. ABITC at concentrations ≥1 μM displayed dose-dependent and selective cytotoxicity to EC cell lines (ECC-1, AN3CA, RL95-2) in comparison to other cancer cell lines. After treatment with ABITC, ECC-1 unlike control cells displayed hallmark features of apoptosis including chromatin condensation and nuclear fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…These changes were still observed after treatment with an antioxidant which, however, could partially block AC‐AM‐induced and ROS‐mediated cell death. This observation is different than the findings by our laboratory to other drugs (e.g., organometallic compound iron(III)‐salophene; ITC derivative ABITC) where ROS generation was the primary mechanism of cytotoxic action in neuroblastoma and endometrial cancer cells and strong activation of p38 and JNK could completely be abolished by cellular co‐treatment with exogenous antioxidants (54,55). Similarly, recent studies suggested that the drug‐induced activation of MAPK including JNK/SAPK and cancer cell apoptosis can be directly ROS dependent (56,57).…”
Section: Discussioncontrasting
confidence: 99%
“…These changes were still observed after treatment with an antioxidant which, however, could partially block AC‐AM‐induced and ROS‐mediated cell death. This observation is different than the findings by our laboratory to other drugs (e.g., organometallic compound iron(III)‐salophene; ITC derivative ABITC) where ROS generation was the primary mechanism of cytotoxic action in neuroblastoma and endometrial cancer cells and strong activation of p38 and JNK could completely be abolished by cellular co‐treatment with exogenous antioxidants (54,55). Similarly, recent studies suggested that the drug‐induced activation of MAPK including JNK/SAPK and cancer cell apoptosis can be directly ROS dependent (56,57).…”
Section: Discussioncontrasting
confidence: 99%
“…Chemotherapy, radiation therapy or their combination is chosen for patients with a medium or high recurrence risk. Most endometrial cancer patients were diagnosed in the early stage and treated with surgery alone or with additional radiation therapy ( 3 ). However, a significant proportion of endometrial cancer patients with metastasis or in the advanced stage still require systematic chemotherapy ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, overall survival remains largely unaffected (3). For patients with advanced stage disease or recurrent disease, particularly when it is not amenable to surgical resection, systemic chemotherapy is often required as adjuvant treatment (4). Therefore, it is beneficial to develop a novel therapeutic agent for patients at risk of micrometastatic disease.…”
Section: Introductionmentioning
confidence: 99%